Principals’ Strategies for Improving Students’ Motivation to Learn - Nur Zatni; Askar Askar; Darmawansyah Darmawansyah (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
This study is in the field of educational management and focuses on the role of school leadership in improving students’ motivation to learn. The purpose of this research is to describe the strategies implemented by the principal of SMA Negeri 1 Moutong in enhancing students’ motivation to learn, as well as to identify supporting and inhibiting factors in the implementation of these strategies. The selection of this topic is based on the importance of school leadership in creating an effective learning environment that can stimulate students’ enthusiasm and academic achievement. This study employs a qualitative descriptive method, with data collected through observation, interviews, and documentation involving the principal, teachers, and students. This study hypothesizes that effective principal leadership strategies significantly increase students’ motivation to learn. The findings reveal that the principal applies several strategies, including providing direct motivation, supervising teaching and learning activities, encouraging innovative teaching methods, giving rewards to high-achieving students, and developing extracurricular activities in collaboration with parents. Supporting factors include teacher collaboration, parental involvement, and adequate school facilities, while inhibiting factors include low student awareness of the importance of education and uncontrolled social media use. The results of this study contribute to the development of educational leadership theory, particularly in strengthening the role of principals in motivating students. In conclusion, principal leadership strategies play a crucial role in enhancing students’ learning motivation and improving the overall quality of education in schools.